Edward Gets Messy - Meade, Rita (New York : Simon & Schuster Books for Young Readers, 2016)
Wearing his perfectly clean suit and living in his perfectly tidy room, Edward the pig avoids getting messy until a big tub of paint falls on his head.
Keywords: Hygiene -- Juvenile fiction; Orderliness -- Juvenile fiction; Swine -- Juvenile fiction; Cleanliness -- Fiction; Pigs -- Fiction